2012
DOI: 10.2166/wst.2012.852
|View full text |Cite
|
Sign up to set email alerts
|

Treating wastewater with high oil and grease content using an Anaerobic Membrane Bioreactor (AnMBR). Filtration and cleaning assays

Abstract: An Anaerobic Membrane Bioreactor (AnMBR) pilot plant was studied to improve certain operational conditions of AnMBRs that treat high oil and grease wastewaters discharged from a snacks factory. A comparison of its performance and behavior was made with an upflow anaerobic reactor throughout the first eight weeks of its operation. Raw snack food wastewater was characterized by oil and grease concentrations of up to 6,000 mg/l, with chemical oxygen demand (COD) and biological oxygen demand (BOD(5)) concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…Constant biogas recirculation rate of 12 LPM was used in the entire study, corresponding to a scouring rate about 15.3 m 3 /m 2 /hr, similar to the reported value 17.6 m 3 /m 2 /hr in the earlier hollow fiber AnMBR study over high strength industrial wastewater (Diez et al, 2012). Over the 140 days study period, the transmembrane pressure (TMP) had increased 2.0 kPa while maintaining constant flux operation at 8 LMH (Figure 3-10).…”
Section: Membrane Filtration Performancesupporting
confidence: 68%
See 1 more Smart Citation
“…Constant biogas recirculation rate of 12 LPM was used in the entire study, corresponding to a scouring rate about 15.3 m 3 /m 2 /hr, similar to the reported value 17.6 m 3 /m 2 /hr in the earlier hollow fiber AnMBR study over high strength industrial wastewater (Diez et al, 2012). Over the 140 days study period, the transmembrane pressure (TMP) had increased 2.0 kPa while maintaining constant flux operation at 8 LMH (Figure 3-10).…”
Section: Membrane Filtration Performancesupporting
confidence: 68%
“…In this study, it was found that the soluble protein at 325 ± 25 mg/L in permeate could not be further biodegraded by anaerobic digestion, which makes up the majority of the COD in effluent. hollow fiber AnMBR operation study (Diez et al, 2012). Over the 90 day study period, the TMP was monitored, and average daily cycle TMP, as well as the determined critical fluxes are reported in Figure 4-16.…”
Section: Extracellular Polymeric Substances (Epss) Characteristicsmentioning
confidence: 99%
“…A high BOD to COD ratio indicates that wastewater can be readily biodegradable because of the high fraction of oxidizable organic materials content. Another example is an AnMBR pilot plant treating snacks factory wastewater with high oil and grease content (Diez, Ramos, & Cabezas, 2012). Several full-scale AnMBRs have been applied to the biological treatment of highstrength wastewater.…”
Section: High-strength Wastewatermentioning
confidence: 99%
“…An intermittent feeding strategy at an OLR of 4.8 g COD L [19]. Diez et al [58] reported that an anaerobic membrane bioreactor (AnMBR) removed 97% of the COD of oil and greasy wastewater (COD of 22 g L −1…”
Section: Integrated Approach: Modified Configurations and Combined Symentioning
confidence: 99%